La règlementation de la décarbonation du transport maritime - Alavoine, Zoé (Aix-Marseille Université, 2022)
Keywords: Droit maritime; Décarbonisation; Transport maritime

La clause merchant - Arista, Pauline (Aix-Marseille Université, 2022)

L'avarie commune - Besse, Ilana (Aix-Marseille Université, 2022)

Le conflit russo-ukrainien : conséquences dans l'industrie maritime et des transports - Faverot Quilichini, Clara (Aix-Marseille Université, 2022)

La responsabilité du manutentionnaire - Hubert, Solène (Aix-Marseille Université, 2022)

Conflict Management over Maritime Territories : Use of ADR in Maritime Disputes: Kenya vs Somalia - Mwala, Natasha Lulia (Universität Wien, 2022)
The recent discoveries of natural resources on both territorial and maritime borders have heightened the probability of conflicts between states specifically in the Horn of Africa and the Greater Lakes Region. As a highly volatile region, conflicts are not a foreign phenomenon which have been plaguing the region since transition to the post-colonial era. It is simple to argue that the cause of disputes is due to the arbitrary borders drawn by the European powers, however, the region is experiencing a contemporary ‘scramble and petition’ with countries racing to exploit and gain over the newfound resources. In addition to this, the rise of nationalist sentiments combined with the burgeoning population and struggle of governments to finance their domestic budgets while trying to reduce borrowing from foreign markets due to the inflation costs which makes it expensive, also plays a key role in the quest to benefit from mineral exploration and excavation. While traditional conflicts rose from land border disputes that escalated to violence especially between border communities, maritime conflicts tend to be handled in legal ways with parties seeking intervention from bodies such as the International Tribunal of the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). Most cases are solved by outright delimitation of the maritime borders rather that joint management of marine land masses or natural resources based on mutual understanding or mutually assured benefits. The recent Kenya-Somalia Maritime dispute is an excellent case study. The aim of this research is to not only show alternative dispute resolution methods that can be used in maritime border disputes but also analyse the switch from pacific means of settlement of disputes to judicial intervention of the court. It begins by looking at the evolution of land border disputes between the two states, touches on the maritime dispute and their diplomatic, economic and security relationship. It further critically analyses the points of view of the two countries and the court’s ruling. Finally, it examines alternative dispute settlement mechanism that could have been used.
Keywords: ICJ; Joint maritime agreement; LOS; Maritime boundary dispute; Maritime délimitation; Memorandum of understanding

L'attractivité du pavillon britannique après le BREXIT - Ramelet, Norine (Aix-Marseille Université, 2022)

La sécurité dans l'exploitation des porte-conteneurs - Vandame, Marie (Aix-Marseille Université, 2022)

Les ventes en sauvetage dans le milieu maritime - Viriot, Lucie (Aix-Marseille Université, 2022)